2000
DOI: 10.1103/physrevb.62.8306
|View full text |Cite
|
Sign up to set email alerts
|

TiO(001) single-crystal film formation by the incorporation of oxygen from MgO into the deposited Ti film

Abstract: The formation of a TiO͑001͒ film on MgO͑001͒ was investigated using metastable impact electron spectroscopy ͑MIES͒, ultraviolet photoelectron spectroscopy ͑He I͒, impact-collision ion scattering spectroscopy, and electron diffraction techniques. It was found that epitaxial TiO films were formed by Ti deposition on the MgO surface followed by annealing at 1000 K. The TiO film formation was related to the incorporation of oxygen from MgO into the deposited Ti film. Metallic properties of the outermost surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Recently, Suzuki et al found that the TiO(1 0 0) single-crystal film can be formed by Ti deposition on MgO(1 0 0) and subsequent annealing at 1000 K [9]. They measured He I UPS spectra for the film, and observed the conduction band and the valence band at the Fermi edge and at 6.5 eV, respectively [9].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Suzuki et al found that the TiO(1 0 0) single-crystal film can be formed by Ti deposition on MgO(1 0 0) and subsequent annealing at 1000 K [9]. They measured He I UPS spectra for the film, and observed the conduction band and the valence band at the Fermi edge and at 6.5 eV, respectively [9].…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Suzuki et al found that a TiO single crystal film can be epitaxially grown on MgO(1 0 0) [8,9]. In order to explore the band structure, however, it is desirable to form the single crystal film on a conductive substrate.…”
Section: Introductionmentioning
confidence: 98%
“…produced by annealing in UHV to ¾1150 K. 25 Moreover, a pronounced Ti 3C 3d signal was seen from a TiO x (x ¾ 1) film on MgO. 26 A possible explanation for the absence of any Ti 3d signal in MIES may come from a recent theoretical analysis of the nature of the extra state created upon the introduction of additional charge to TiO 2 110 . 22 On the basis of firstprinciples density functional theory (DFT) calculations it was concluded that for Na adsorption the extra state is essentially localized on substrate Ti cations, with a dominant weight on those lying in the subsurface plane, just below the surface fivefold-coordinated Ti species.…”
Section: Discussion and Interpretation Delocalization Of The Excess Cmentioning
confidence: 97%
“…4). Earlier reports show TiO (0 0 1) single crystal films have been deposited on MgO substrates [10].…”
Section: Resultsmentioning
confidence: 99%